Production-Comprehension Asymmetries in Child Language 2011
DOI: 10.1515/9783110259179.39
|View full text |Cite
|
Sign up to set email alerts
|

An asymmetry in the acquisition of accusative clitics in child Romanian

Abstract: anonymous reviewer points out that experimental data were related, in most cases, to binding theory, which might explain the focus on 3 rd person accusative clitics and refl exive clitics. This is indeed the case for several studies (Jakubowicz 1989; Baauw 2000; Hamann 2002, a.m.o.). It is equally true that in some previous studies relying on longitudinal data one can reconstruct from the tables the difference between the acquisition of 1 st , 2 nd and 3 rd person accusative clitics. What we noticed, though, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In contrast to the bulk of studies discussed above, few investigations have been conducted of clitics in typically developing French other than those of the 3rd person (except for Hamann et al, 1996, who counted all accusative clitics and Tuller et al, 2011 described below). For other Romance languages, a few authors have observed an asymmetric development between 3rd person (5) and 1st/2nd person ACC (6), with the former emerging slower than the latter (Avram and Coene, 2008;Baauw, 2000;Coene and Avram, 2011;Gavarró and Fortó n, 2014;Silva, 2010;Tsimpli and Mastropavlou, 2007): 5Jean le/la regarde John him/her looks-at 'John is looking at him/her' 6Jean me/te regarde John me/you looks-at 'John is looking at me/you' Coene and Avram (2011) analyzed longitudinal corpora of the speech of two monolingual Romanian children (aged 1;05--3;05) and found that in obligatory clitic contexts, ACC of the third person were frequently omitted until age 3 years, while those of the first and second person were always present from the earliest utterances. This asymmetric omission pattern was also observed for very young Catalan-speaking children (Gavarró and Fortó n, 2014), for Greek-speaking children with SLI aged 3;5 to 7 (Tsimpli, 2001) and for adult L2 learners (Tsimpli and Mastropavlou, 2007).…”
Section: Rd Person Vs 1st Person Accmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the bulk of studies discussed above, few investigations have been conducted of clitics in typically developing French other than those of the 3rd person (except for Hamann et al, 1996, who counted all accusative clitics and Tuller et al, 2011 described below). For other Romance languages, a few authors have observed an asymmetric development between 3rd person (5) and 1st/2nd person ACC (6), with the former emerging slower than the latter (Avram and Coene, 2008;Baauw, 2000;Coene and Avram, 2011;Gavarró and Fortó n, 2014;Silva, 2010;Tsimpli and Mastropavlou, 2007): 5Jean le/la regarde John him/her looks-at 'John is looking at him/her' 6Jean me/te regarde John me/you looks-at 'John is looking at me/you' Coene and Avram (2011) analyzed longitudinal corpora of the speech of two monolingual Romanian children (aged 1;05--3;05) and found that in obligatory clitic contexts, ACC of the third person were frequently omitted until age 3 years, while those of the first and second person were always present from the earliest utterances. This asymmetric omission pattern was also observed for very young Catalan-speaking children (Gavarró and Fortó n, 2014), for Greek-speaking children with SLI aged 3;5 to 7 (Tsimpli, 2001) and for adult L2 learners (Tsimpli and Mastropavlou, 2007).…”
Section: Rd Person Vs 1st Person Accmentioning
confidence: 99%
“…Their complexity has positioned them as a clinical marker of specific language impairment or 'SLI' (Paradis et al, 2003;Parisse and Maillart, 2004) and more generally of atypical language development (Delage, 2008;Tuller et al, 2011). More recently, it has been suggested for Greek, Romanian and Catalan that not all ACC are equally difficult (Avram et al, 2015;Coene and Avram, 2011;Gavarró and Fortó n, 2014;Tsimpli and Mastropavlou, 2007). Instead what appears to be problematic is specifically 3rd person clitics, while 1st and 2nd person ACC prove to be relatively simpler.…”
Section: Introductionmentioning
confidence: 99%
“…Prosodic/phonological explanations have been challenged by studies comparing the production of 3DO clitics to the production of functional morphemes with identical prosodic/phonological features, such as determiners, reflexive clitics, subject clitics and first and second person DO clitics. According to these studies, children have less problems in the production of reflexive clitics, subject clitics and definite determiners (Hamann et al, 1996;Jakubowicz et al, 1998;Bedore and Leonard, 2001;Audollent and Tuller, 2003;Smith et al, 2008;Zesiger et al, 2010;Gavarró, 2012;Arosio et al, 2014), and they have less problems with the production of first and second person DO clitics (Tsimpli and Mastropavlou, 2007;Zesiger et al, 2010;Coene and Avram, 2011;Tuller et al, 2011;Gavarró and Fortón, 2014;Delage et al, 2016).…”
Section: The Acquisition Of 3do Cliticsmentioning
confidence: 99%
“…In contrast to the vast amount of studies that have focused on third person accusative clitics in TD and SLI, few investigations have been conducted for clitics other than those of the third person. However, authors who have examined first person clitics have observed that they emerge earlier than those of the third person (2), (Tsimpli & Mastropavlou, 2007;Avram & Coene, 2008;Coene & Avram, 2011;Author & Coauthors, to appear A c c e p t e d M a n u s c r i p t 11 children with SLI aged 3;5 to 7 years (Tsimpli, 2001) and for adult L2 learners (Tsimpli & Mastropavlou, 2007 A c c e p t e d M a n u s c r i p t 12 -masculine, la -feminine), although not on ACC1 (me -either masculine or feminine).…”
Section: Accusative Clitic Pronouns and Their Acquisitionmentioning
confidence: 99%